Gummy Candy Nanosimplia Kombinasi Batang Buah Nenas (Ananas comosus) dan Buah Melon (Cucumis melo L.) sebagai Pengobatan Sariawan - Romi Ramadiansyah; Rika Syahpitri; Viola Fransetya Dewi; Rahma Shintauli; Latifa Anum; Fadilla Dwi Yanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Canker sores are an inflammation of the oral tissues, generally caused by bacterial and fungal infections. They can cause pain and discomfort and reduce the sufferer's quality of life. Treatment for canker sores has been dominated by synthetic drugs, but they are less popular among the public, especially children, due to discomfort and concerns about side effects. Therefore, we need safer and more easily accepted alternative treatments based on culturally derived materials. This study is to investigate the potential of pineapple and melon stems formulated in the form of gummy candy nanosimplicia as a complementary therapy in the treatment of canker sores. The research method was carried out through a literature review by collecting scientific articles from the PubMed, ScienceDirect, and Google Scholar databases, then analyzed using VOSviewer software to map emerging research trends and potential. The analysis results indicate that there are approximately 600 articles discussing the active metabolite content in pineapple and melon stems that have antibacterial and antifungal activity, as well as the development of innovative preparations such as gummy candy as a delivery medium for bioactive compounds. The implications of this study indicate that the combination of pineapple stem and melon nanosimplisia has the potential to be developed as a safe, attractive, and effective natural herbal candy product for the prevention and treatment of mouth ulcers, especially in children.